FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP KINERJA UMKM DI KOTA TEGAL - Ida Farida; Sunandar Sunandar; Aryanto Aryanto (Monex: Journal of Accounting Research, 2019)
Tegal City has many small and medium industries. The development of UMKM in Tegal City increases the absorption of the highest labor compared to other business units (Department of Industry and Trade, Cooperatives and UMKM, Tegal City, 2015). To continue to develop UMKM in Tegal City must be able to improve competitiveness and self quality so that the performance of UMKM can also increase.Educational background is an important capital in determining the quality of human resources so that it will produce high quality and competitive products. Continuity of business development and progress is influenced by the educational background of UMKM entrepreneurs. With quality human resources will create new and innovative creations. Innovative and quality products will certainly increase competitiveness with products from outside. . The use of e-commerce systems in the marketing process of UMKM products is an important factor in improving the performance of UMKM. With e-commerce UMKM entrepreneurs can increase and expand market share and increase sales. This study aims to determine the effect of the ability to prepare financial statements, educational background and interest in using e-commerce on the performance of UMKM in Tegal City.